Pengaruh Penggunaan Model Guided Inquiry Yang Berbantuan Media Video Terhadap Minat Belajar Siswa Pada Pelajaran IPAS Kelas V SD Inpres 8 Mamboro - Putri Legiani Purnamaning; Zulnuraini Zulnuraini; Nur Rahma (JURNAL DIKDAS, 2025)
This study aims to determine the effect of implementing the Guided Inquiry learning model on students' learning interest in science subjects for grade V of SD Inpres 8 Mamboro. This type of research is a quantitative experimental research using the Quasi Experiment method with Quasi Experimental Design. The subjects in this study were 50 students consisting of 25 students of class VA SD Inpres 8 Mamboro as the experimental class, and 25 students of class VB SD Inpres 8 Mamboro as the control class. Data collection was carried out using research instruments in the form of. The data analysis used primary data, where the data was obtained directly by researchers in the field through respondents by distributing student learning interest questionnaires and secondary data in the form of evidence, notes or historical reports that had been arranged in archives or documentary data 0.014 <0.05 then the influence of Ha and no influence of Ho, meaning that there is an influence of the application of the Guided inquiry learning model on students' learning interest in the subject of science in class V SD Inpres 8 Mamboro. So it can be concluded that the Guided inquiry learning model has an effect on students' learning interest in the subject of science in class V SD Inpres 8 Mamboro